2022
DOI: 10.1088/2515-7655/ac9808
|View full text |Cite
|
Sign up to set email alerts
|

Water driven phase transitions in Prussian white cathode materials

Abstract: Prussian White (PW, Na2Fe[Fe(CN)6]∙zH2O) is a promising cathode material for use in sodium-ion batteries (SIBs) for large-scale energy storage applications which demand long cycling life-times. For use in non-aqueous battery applications PW must not contain any water, and yet its removal induces a large volume change destabilizing the structure and reducing cycling life. Indeed, the material undergoes multiple phase transitions depending upon both the sodium and water content. Due to the extensive use of X ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Indeed, a more recent study supports our findings on the reduction of the unit cell upon dehydration. 31 W. R. Brant et al 29 suggested a volume collapse of 20% relatively to the hydrated phase. In this study, the dehydration conducted under dynamic vacuum conditions (10 −2 mbar, at 170 °C) leads to a lower volume contraction of ∼6%, which is reflected in a loss of crystallinity (observed as an increase of the FWHM of the diffraction peaks – see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a more recent study supports our findings on the reduction of the unit cell upon dehydration. 31 W. R. Brant et al 29 suggested a volume collapse of 20% relatively to the hydrated phase. In this study, the dehydration conducted under dynamic vacuum conditions (10 −2 mbar, at 170 °C) leads to a lower volume contraction of ∼6%, which is reflected in a loss of crystallinity (observed as an increase of the FWHM of the diffraction peaks – see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rudola et al 30 made important remarks highlighting structural conversion and stability when Fe-based PBA is thermally dehydrated converting from monoclinic to the higher capacity rhombohedral structure emphasising its sensitivity towards drying pressure, gas atmosphere and working environment. More recent study by Nielsen et al 31 investigated the effect of water removal on a Prussian White (PW) system by using neutron diffraction observing the co-existence of the monoclinic and hydrated rhombohedral structures for a single composition of PW independently of the synthesis method adding on to the inherent understanding of water in the structure. While most of the research has focussed on the understanding of the dehydration at the material level, in this study we further push the investigation from materials to composite electrodes processed in water.…”
Section: Introductionmentioning
confidence: 99%
“…Prussian blue analogues (PBAs) are of interest as Na-ion cathode materials, and the presence of water is known to impact the structure and properties of PBAs. 41,42 Characterisation using Xrays is particularly challenging, as they contain elements with a similar number of electrons; C and N, H 2 O and Na, as well as the transition metals. Therefore, neutrons are a particularly useful tool in characterising the structure including the location of water as exemplified in a recent study.…”
Section: Neutron Diffraction Experimentsmentioning
confidence: 99%
“…Therefore, neutrons are a particularly useful tool in characterising the structure including the location of water as exemplified in a recent study. 42 Neutron diffraction was used to investigate the impact of water on the structure of Prussian white, a Na rich PBA. Fourier difference maps were used to locate the H 2 O oxygen within the framework, understand how this influences the overall structure, and therefore improve synthetic control over the structure and electrochemical properties of this family of cathode materials.…”
Section: Neutron Scatteringmentioning
confidence: 99%
“…Please note that synthesized Prussian White materials always contain a finite amount of water which is extremely hard to remove. Yet, changes in the water content can modify the orbital levels of the iron centers and even lead to a transition from monoclinic to rhombohedral structures [34,35] . However, we concentrate on the unperturbed system here as, first, we are interested in the properties of ideal system, and second, because the computationally very demanding systematic study of structural water in battery materials [36] is beyond the scope of the present paper.…”
Section: Introductionmentioning
confidence: 99%